SYNTHESIS OF TETRA-p-PROPENYLTETRAESTERCALIX[4]ARENE AND TETRA-p-PROPENYLTETRACARBOXYLICACIDCALIX[4]ARENE FROM p-t-BUTYLPHENOL - Triana Kusumaningsih; Jumina Jumina; Dwi Siswanta; Mustofa Mustofa (Indonesian Journal of Chemistry, 2010)
A research has been conducted to synthesize tetra-p-propenyltetraestercalix[4]arene and tetra-p-propenyltetracarboxylicacidcalix[4] arene using p-t-butylphenol as a starting material. The synthesis was carried out in following stages, i.e (1) synthesis of p-t-butylcalix[4]arene from p-t-butylphenol, (2) debutylation of p-t-butylcalix[4]arene, (3) tetraallilation of 25,26,27,28-tetrahydroxycalix[4]arene with NaH and allilbromida in dry tetrahydrofuran, (4) Claissen rearrangement of 25,26,27,28-tetrapropenyloxycalix[4]arene, (5) esterification of tetra-p-propenyltetrahydroxycalix[4]arene, (6) hydrolisis of tetra-p-propenyltetraestercalix[4]arene. The all structures of products were observed by means of melting point, FTIR, and 1H-NMR spectrometers. Tetra-p-propenyltetraestercalix[4]arene compound was obtained as yellow liquid product in 55.08% yield. Tetra-p-propenyltetracarboxylicacidcalix[4]arene compound was obtained as white solid product with the melting point 135-137 °C at decomposed and in 70.05% yield.